Study on vehicle active suspension system control method based on homogeneous domination approach. Issue 1 (12th September 2019) - Meng, Qinghua; Chen, Chih‐Chiang; Wang, Pan; Sun, Zong‐Yao; Li, Bingji
Abstract: In an active suspension system, there is an actuator mounted between the sprung mass and the unsprung mass to change the stiffness and damp of the suspension for ride comfort and handling stability. Because the active suspension control system is an under‐actuated system, the control problem of the active suspension is challenging but interesting. In order to solve this issue, a novel vehicle active suspension control method based on homogeneous domination approach is proposed in this paper. Firstly, a groundhook control model is constructed according to the general active suspension dynamic model. In order to deal with the additional terms of the control system which are harmful for convergence, a homogeneous domination approach is used to construct an active suspension homogeneous controller (ASHC). A useful technical theorem is proposed in the stability analysis to show that the proposed ASHC can guarantee the states of the active suspension system being stabilized. Compared with the SMC method and without any controller (passive suspension), the simulation results indicate that the proposed ASHC is effective.